Morphology and dynamics of self-assembled structures in mixed surfactant systems (SDS plus CAPB) in the context of methane hydrate growth - Hande, Vrushali; Choudhary, Nilesh; Chakrabarty, Suman; Kumar, Rajnish (Journal of Molecular Liquids, 2020)
Presence of small dosages of surfactants in the aqueous phase has been reported to enhance the rate of gas hydrate (clathrate) formation. In this work, using extensive atomistic molecular dynamics (MD) simulations, we have investigated how SDS (surfactant) aggregates in the presence/absence of CAPB (co-surfactant) at ambient conditions (temperature 298 K and pressure 1 bar) and at hydrate forming conditions (temperature 275 K and pressure 50 bar) resulting in altered growth kinetics of methane hydrate. We observe that SDS forms aggregates of different sizes and shapes depending on the thermodynamic condition starting from random distributions of the surfactants. In the presence of the CAPB co-surfactant, tightly packed mixed aggregates are formed. Using various structural order parameters, we demonstrate that shape of the aggregates deviates from spherical as well as cylindrical symmetry. During the aggregation process in presence of methane, the methane molecules get absorbed into the aggregates, enhance the aggregation kinetics and provide structural flexibility to the aggregates. This result is partly in agreement with previous experimental observations that SDS (with or without a co-surfactant) may form micelle-like structures under hydrate forming conditions and that methane gets absorbed by these aggregates leading to enhanced solubility of methane in the aqueous phase. Further, we have investigated the dynamics of shape fluctuations of the aggregates and observed that several distinct relaxation timescales exist in these heterogenous systems. (C) 2020 Elsevier B.V. All rights reserved.